Estudo do papel do periventrículo posterior na neurogênese pós-lesional - Santana, Aline Dos Santos [UNIFESP] (2019)
This study aimed to analyze the role of PVP in neurogenesis after transient global ischemia in saline or choline treated rats. Scanning and transmission electron microscopy were used for the morphological characterization of PPV. The occurrence of neurogenesis in PVP was assessed through immunostaining for BrdU. BrdU immunostaining was not conclusive due to the heterogeneity of response among animals and groups and also due to the lack of resolution of light microscopy. The morphological characterization of PPV revealed a slight rarefaction of ciliary tufts of animals submitted to ischemia when compared to normal animals. No differences were identified between saline- or choline-treated ischemic animals. Morphological characterization revealed the secretion of vesicles by the ependymal cilia both in the PVP and the lateral ventricle. Size and concentration of particles in the cerebrospinal fluid was confirmed by Nano Tracker Analysis. Our results are unprecedented and bring innovative potential regarding the role of extracellular vesicles in both the physiology and pathogenesis of the nervous system. These data may also contribute to the development of new technologies for diagnosis and therapy of chronic degenerative diseases.